PEMANFAATAN PEKARANGAN RUMAH UNTUK TANAMAN OBAT KELUARGA SEBAGAI GERAKAN MASYARAKAT HIDUP SEHAT DI PUSKESMAS DADOK PADANG - Yuanita Ananda; Mulyanti Roberto Muliantino; Zifriyanthi Minanda Putri; Muthmainnah Muthmainnah; Edo Gusdiansyah (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
During this Covid-19 pandemic, physical activity and utilizing the yard for family medicinal plants is highly recommended because it can increase one's body immunity and will reduce the spread of Covid-19 disease. Physical activity and family medicinal plants is one of the programs of the Healthy Living Community Movement. This program is one of the programs that have been launched by the Government. The results of a survey conducted in the Dadok Tunggul Hitam Public Health Center, Padang District, Koto Tangah, it is known that most people rarely do physical activity that can improve the body's immune system. The implementation of activities is carried out directly by implementing strict health protocols. The activity started by doing physical activity in the form of aerobic exercise and giving and explaining the types and benefits of family medicinal plant seeds to 15 family heads where 1 family head got 5 family medicinal plant seeds. The evaluation results showed that there was an increase in public knowledge about the importance of gymnastics. Aerobics and the types and benefits of family medicinal plants during the pre test and post test. Suggestions for the public health centers are to monitor the results of this education